2017
DOI: 10.1128/jvi.01445-16
|View full text |Cite
|
Sign up to set email alerts
|

Creating an Artificial Tail Anchor as a Novel Strategy To Enhance the Potency of Peptide-Based HIV Fusion Inhibitors

Abstract: 20 (enfuvirtide) and other peptides derived from the human immunodeficiency virus type 1 (HIV-1) gp41 C-terminal heptad repeat (CHR) region inhibit HIV fusion by binding to the hydrophobic grooves on the N-terminal heptad repeat (NHR) trimer and blocking six-helix-bundle (6-HB) formation. Several strategies focusing on the binding grooves of the NHR trimer have been adopted to increase the antiviral activity of the CHR peptides. Here, we developed a novel and simple strategy to greatly enhance the potency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…However, HIV-1 with E49K mutation in the gp41 NHR became resistant to HP23 [ 24 ]. In our previous study, we identified a shallow pocket (N-pocket) in the N-terminal region of the NHR domain ( Figure 1 b) and found that addition of an IDL-anchor to the C-terminus of a CHR-peptide could significantly improve the peptide’s anti-HIV-1 potency and resistance profile ( Figure 1 c) [ 27 ]. Therefore, we proposed that the addition of an IDL-anchor to the C-terminus of HP23 could result in more stable binding of this peptide with the groove on the NHR-trimer since its N- and C-terminal anchors could bind to the C- and N-pockets on the NHR-trimer, respectively ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, HIV-1 with E49K mutation in the gp41 NHR became resistant to HP23 [ 24 ]. In our previous study, we identified a shallow pocket (N-pocket) in the N-terminal region of the NHR domain ( Figure 1 b) and found that addition of an IDL-anchor to the C-terminus of a CHR-peptide could significantly improve the peptide’s anti-HIV-1 potency and resistance profile ( Figure 1 c) [ 27 ]. Therefore, we proposed that the addition of an IDL-anchor to the C-terminus of HP23 could result in more stable binding of this peptide with the groove on the NHR-trimer since its N- and C-terminal anchors could bind to the C- and N-pockets on the NHR-trimer, respectively ( Figure 1 c).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has shown that addition of an MT anchor and an IDL anchor to the N- and C-termini of the peptide WQ, respectively, results in generation of a new peptide, designated MT-WQ-IDL, with significantly improved inhibitory activity against HIV-1 Bal infection (IC 50 = 0.6 nM) [ 27 ]. It was reported that addition of a glutamic (E) residue to the N-terminus of a CHR-peptide with MT-hook could stabilize the MT hook structure [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction data sets for SC29EK/N36 were collected at beamline BL-19U1 at the Shanghai Synchrotron Radiation Facility, China. The phasing problem was solved by the molecular replacement method using the software CCP4i with a crystal structure of HIV gp41 core (PDB accession number 5H0N) as a searching model (45,46). The final model was manually adjusted in COOT based on the electron density map and refined with the program PHENIX (47,48).…”
Section: Discussionmentioning
confidence: 99%